2022
DOI: 10.1101/2022.05.10.491306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever

Abstract: Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis- aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(93 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, ITA potently restricted C. burnetii axenic growth, indicating a direct inhibitory effect by ITA on C. burnetii. Our findings with IRG1 and ITA restricting C. burnetii replication within murine macrophages are in agreement with recent findings by another group (68). They found that C. burnetii infection induced IRG1 expression in a MyD88-dependent manner, and that IRG1 and ITA restrict C. burnetii replication within murine macrophages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, ITA potently restricted C. burnetii axenic growth, indicating a direct inhibitory effect by ITA on C. burnetii. Our findings with IRG1 and ITA restricting C. burnetii replication within murine macrophages are in agreement with recent findings by another group (68). They found that C. burnetii infection induced IRG1 expression in a MyD88-dependent manner, and that IRG1 and ITA restrict C. burnetii replication within murine macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Our data indicate that TNF is the likely candidate cytokine produced downstream of TLR/MyD88 signaling that drives IRG1 expression. Furthermore, they also found that Irg1 -/mice have a defect in control of C. burnetii infection in vivo and treatment of Irg1 -/mice with ITA reduced C. burnetii bacterial loads (68). Interestingly, they found that human macrophages produce much less itaconate than murine macrophages, which may explain why human macrophages are much more permissive for C. burnetii replication than murine macrophages (68).…”
Section: Discussionmentioning
confidence: 99%